Bio‐priming seeds with cyanobacteria: effects on native plant growth and soil properties. (6th November 2019) - Chua, Melissa; Erickson, Todd E.; Merritt, David J.; Chilton, Angela M.; Ooi, Mark K. J.; Muñoz‐Rojas, Miriam
Abstract : Cyanobacteria are photosynthetic bacteria that form a fundamental part of soil biocrusts, enhance soil function and structure, and can promote plant growth. We assessed the potential of cyanobacteria as a seed bio‐primer for mine‐site restoration in an arid region in Western Australia, examining its effects on native plant growth and the characteristics of mine soil substrates used in dryland restoration. Cyanobacteria strains indigenous to the study region ( Leptolyngbya sp., Microcoleus sp., Nostoc sp., and Scytonema sp.) were used to create an inoculant. Seeds of seven native plant species were bio‐primed with the inoculant, and their germination and growth assessed in a laboratory experiment. Seedling growth after bio‐priming was assessed in a glasshouse experiment for a subset of three species, in two different substrates (topsoil and mine waste). Soil properties related to soil function, e.g. total organic carbon, total nitrogen, and microbial activity, were also measured. Minor effects on germination were recorded with only significantly higher germination rates reported in E. gamophylla . Soil parameters were generally higher in topsoil than in mine waste, regardless of bio‐priming treatment. However, bio‐priming resulted in seedlings of four species producing longer radicles and/or shoots. For example, seedling root lengths of bio‐primed G. wickhamii were 57% larger than the control treatment (30.1 ± 4.3 and 13.0 ± 1.6 mm, respectively); and shoots of T. wiseana were 54% longer in the bio‐primed treatment (18.6 ± 1.6 mm) compared to the control (8.53 ± 1.4 mm). Overall, our results highlight that bio‐priming with cyanobacteria may improve plant growth for some species commonly used in dryland restoration.